An Evaluation of Extensive Reading Program : Principle Conformity and Increasing of Students Reading Habit - Zamratul Khairani; Gusti Milla Quaidy; Ramya Tulasi Dega (Modality Journal: International Journal of Linguistics and Literature, 2022)
This research aims to discover whether extensive reading has fulfilled the extensive reading program principle and whether the program is able to emerge reading habit. This research was conducted due to the evaluation of an extensive reading program that has rarely been done and the program has not significantly been able to increase library visits as an indication of good reading. This research will provide insight for educators, decision makers and students about the implementation of extensive reading programs so that programs can be carried out better. This research is descriptive research which is categorized into qualitative research. data obtained through observation and group interviews. data was analyzed using Miles and Hubberman models. research found extensive reading has not fully fulfilled the extensive reading principles. Some students struggle with reading, wherein there is a lot of difficult vocabulary. Besides, students' reading habits have emerged. students are glad to read online through a reading application.Penelitian ini bertujuan untuk mengetahui apakah program extensive reading telah melaksanakan prinsip extensive reading serta apakah program mampu memunculkan kebiasaan membaca siswa. Penelitian dilaksanakan karena evaluasi program extensive reading jarang dilaksanakan serta program tersebut belum dapat meningkatkan kunjungan ke perpustakaan secara signifinikan dimana ini merupakan indikasi meningkatnya kecintaan peserta didik untuk membaca. penelitian ini akan memberikan wawasan kepada pendidik, pembuat keputusan dan peserta didik tentang pelaksanaan program sehingga program dapat dilaksanakan dengan lebih baik. penelitian ini merupakan penelitian deskriptif yang merupakan penelitian kualitatif. data diperoleh melalui pengamatan dan wawancara kelompok. data dianalisis menggunakan model Miles and Huberman. Hasil penelitian menunjukkan program extensive reading belum sepenuhnya memenuhi kriteria extensive reading. beberapa peserta didik masih kesulitan dalam membaca dimana banyak kosakata yang sulit ditemukan. Selain itu, kebiasaan membaca peserta didik sudah mulai muncul. peserta didik menyenangi membaca daring melalui aplikasi membaca.